Complex technology of secondary aluminium alloys quality increasing - I. P. Volchok; A. A. Mityayev; R. A. Frolov (Литьë и металлургия)
In the article the possibility of obtaining high-quality castings from a charge, consisting of secondary aluminium A356.2 and AK7ch with a high level of iron, is considered. The influence of the complex treatment of the melt by a modifier and fine-crystalline remelting at an iron content in the alloy to 1.84% is presented.